2015
DOI: 10.3892/ol.2015.3450
|View full text |Cite
|
Sign up to set email alerts
|

Metformin inhibits growth of lung adenocarcinoma cells by inducing apoptosis via the mitochondria-mediated pathway

Abstract: Abstract. Metformin is commonly used to treat type II diabetes, although it may also reduce the risk of cancer and improve the associated prognosis. However, its mode of action in cancer remains unclear. The present study evaluated the effects of metformin on lung adenocarcinoma A549 cells and identified molecular mechanisms of metformin activity. The A549 cells were treated with metformin at different concentrations and cell viability was assayed by using an MTT assay. The cell cycle and the apoptosis rate we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 28 publications
2
29
0
1
Order By: Relevance
“…Metformin, which is a member of the biguanide family, is predominantly used for the treatment of type 2 diabetes by increasing insulin sensitivity (13). Recently, epidemiologists discovered that diabetic patients who were treated with metformin had a lower risk, and lower incidence, of multiple types of cancer (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Metformin, which is a member of the biguanide family, is predominantly used for the treatment of type 2 diabetes by increasing insulin sensitivity (13). Recently, epidemiologists discovered that diabetic patients who were treated with metformin had a lower risk, and lower incidence, of multiple types of cancer (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that metformin could inhibit cell proliferation in several cancer cells in vitro [57]. However, the effect and mechanism of metformin on cell proliferation in some certain cancer cells remain poorly understood.…”
Section: Resultsmentioning
confidence: 99%
“…Relative to tumor size in vivo after treatment with metformin, Wang et al [51], demonstrated that xenograft tumor from lung adenocarcinoma A549 cells treated with metformin (200 mg/kg/day) was signifiantly decreased in size. The same was observed in a study of Tsutsumi et al [52] that showed a tumor volume significantly decreased after treatment with metformin compared with the control in animal xenografic model with prostate cancer cell line LNCaP.…”
Section: Discussionmentioning
confidence: 99%